A narrativa poético-musical em Gênesis, Ronco da Cuíca, Tiro de Misericórdia e Escadas da Penha: a performance liminar de João Bosco no medley gravado no disco 100ª Apresentação - Renata Vanucci Carvalho (2017)
This research aims to analyze the performance and the poetical and musical narrative of the pout-pourri Gênesis, O Ronco da Cuíca, Tiro de Misericórdia e Escadas da Penha recorded by the singer, composer and guitar player João Bosco in the alive album 100a Apresentação (1983). In this masterpiece Bosco and Aldir Blanc tell the story of a Jesus Christ from the slum through the junction of the mentioned songs. Concepts drawn from Cultural Anthropology, in particular the concept of Liminality seen in Victor Turner, Van Gennep and Richard Schechner, were central for this analysis. Furthermore the references of musical analysis in Dante Grela, poetical analysis in Paul Zumthor and the concepts developed and exploited by the theorist and theater director Jerzy Grotowski were used in order to enlighten some aspects such as music, text, culture and performance that make this masterpiece exceptional and revealing of the ritual dimension of the musical performance. Inspired by the process of building this research and its results the author also intents to evaluate her own work as an artist and performer always in the quest for a transforming performance like it is the one developed by João Bosco in the pout-pourri taken as the object of this paper.